2020
DOI: 10.1149/1945-7111/abc767
|View full text |Cite
|
Sign up to set email alerts
|

The Dissolution Dilemma for Low Pt Loading Polymer Electrolyte Membrane Fuel Cell Catalysts

Abstract: Cost and lifetime currently hinder widespread commercialization of polymer electrolyte membrane fuel cells (PEMFCs). Reduced electrode Pt loadings lower costs; however, the impact of metal loading (on the support) and its relation to degradation (lifetime) remain unclear. The limited research on these parameters stems from synthetic difficulties and lack of in situ analytics. This study addresses these challenges by synthesizing 2D and 3D Pt/C model catalyst systems via two precise routes and systematically va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 69 publications
7
38
0
Order By: Relevance
“…Pt dissolution studies obtained at a constant loading of 30 wt.% of precious metal and show that without further effort to improve the stability of the smallest NPs, high‐power performance devices obtained by increasing Pt utilization and dispersion will not be possible by further decreasing particle sizes. However, similar Pt dissolution studies performed with constant particle size, but decreasing interparticle distance showed a trend of decreasing detected Pt dissolution at decreasing interparticle distance [56] . Such studies had not been possible using commercial catalyst materials.…”
Section: Preparation Of Supported Catalysts From Colloidsmentioning
confidence: 91%
See 1 more Smart Citation
“…Pt dissolution studies obtained at a constant loading of 30 wt.% of precious metal and show that without further effort to improve the stability of the smallest NPs, high‐power performance devices obtained by increasing Pt utilization and dispersion will not be possible by further decreasing particle sizes. However, similar Pt dissolution studies performed with constant particle size, but decreasing interparticle distance showed a trend of decreasing detected Pt dissolution at decreasing interparticle distance [56] . Such studies had not been possible using commercial catalyst materials.…”
Section: Preparation Of Supported Catalysts From Colloidsmentioning
confidence: 91%
“…Finally, with an optimized control of the size and the conditioning steps, the toolbox was recently used to independently investigate the influence of NP size and metal loading (interparticle distance) on the stability of electrocatalysts against metal dissolution [46,56] . Pt dissolution studies obtained at a constant loading of 30 wt.% of precious metal and show that without further effort to improve the stability of the smallest NPs, high‐power performance devices obtained by increasing Pt utilization and dispersion will not be possible by further decreasing particle sizes.…”
Section: Preparation Of Supported Catalysts From Colloidsmentioning
confidence: 99%
“…When aiming at ultra-low Pt loadings for PEMFC,i ti s crucial to discuss the impact of the catalyst loading on Pt dissolution. Previous works in this field [10,11,17] have always been conducted on model surfaces.Realistic catalyst layers on gas diffusion layers (GDL) with relevant loadings for fuel cell applications have not yet been directly investigated. Figure 2 shows the impact of catalyst loading on the dissolution of Pt in realistic catalyst layers studied with the novel GDE-ICP-MS setup.T he corresponding additional structural characterization and electrochemical data can be found in Figures S4-S8.…”
Section: Resultsmentioning
confidence: 99%
“…When aiming at ultra‐low Pt loadings for PEMFC, it is crucial to discuss the impact of the catalyst loading on Pt dissolution. Previous works in this field [10, 11, 17] have always been conducted on model surfaces. Realistic catalyst layers on gas diffusion layers (GDL) with relevant loadings for fuel cell applications have not yet been directly investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Follow up work has demonstrated an improvement in ORR activity at small interparticle distance also for carbon supported high surface area electrocatalysts 36 . Very recently, it has been shown that the inter-particle distance of Pt nanoparticles deposited on two dimensional as well as three dimensional carbon supports influences the amount of dissolved Pt detected in scanning flow cell (SFC) measurements coupled to online ICP-MS 12 . Density functional theory modeling indicates that proton accumulation caused by the overlap of the EDL (at high particle density) competes with proton depletion caused by the proximity of the nanoparticles to the carbon support 37 .…”
Section: Introductionmentioning
confidence: 99%